Bacterial sensitivity profile in a public hospital in Teresina (Research, Society and Development, 2021)
The objective of this study was to analyze the profile of bacterial sensitivity through reports of cultures collected from patients in the Intensive Care Unit (ICU), showing the direction for therapeutic conduct. This is a descriptive, retrospective study with a quantitative approach to cultures of urine, blood and tracheal secretions. The sample consisted of 330 reports of positive cultures from patients hospitalized from February 1, 2019 to February 1, 2020 in the ICU of the Emergency Hospital of Teresina Dr. Zenon Rocha. Of the total number of reports analyzed, 227 (68.50%) were positive for tracheal secretion, 71 (21.50%) for blood culture and 32 (9.70%) for urine culture. Pseudomonas aeruginosa being the most prevalent in tracheal secretion, Acinetobacter coagulase negative in blood cultures and Klebsiella pneumoniae in urine cultures. Therefore, the results obtained followed the pattern of similar studies carried out in other locations, with particularities arising from the epidemiology of the region studied.